Effectiveness of Zakat Management at BAZNAS North Lombok Regency - Arifin, Ernaldo Fikrul; Alwyah, Lila (Business Management, 2026)
Effective zakat management is a key indicator of the success of zakat institutions in carrying out their social functions and empowering the community's economy. This study aims to analyze the effectiveness of zakat management at the National Zakat Agency (BAZNAS) of North Lombok Regency through indicators of collection, distribution, utilization, transparency, and its impact on mustahiq (recipients of zakat). Using a descriptive qualitative approach with observation, interviews, and documentation techniques, this study found that the number of muzaki has fluctuated in the last three years, while the number of mustahiq has increased significantly from 2,996 in 2022 to 6,897 in 2024. BAZNAS programs in the fields of humanity, health, education, da'wah, and the economy have shown quite high effectiveness, especially in the aspects of data collection, distribution, and empowerment. However, the increase in mustahiq emphasizes the need for innovation in the utilization of productive zakat and strengthening zakat literacy in the community. Overall, BAZNAS North Lombok has demonstrated transparent, accountable, and socially impactful performance, but still requires optimization in the aspect of transforming mustahiq into muzaki.